Gonadal histology of the tiger barb Puntius tetrazona (Cyprinidae) - Arman, Sezgi; İşisağ Üçüncü, Sema (Journal of Fisheries, 2020)
The ornamental fish industry constitutes a big portion of the economy in many countries of the world. Thousands of attractive fish species are traded annually. The tiger barb Puntius tetrazona is one of the most charming freshwater aquarium species worldwide. The present paper aimed at expanding the knowledge of the reproductive biology of this tropical fish. The ovary and the testis tissues of the tiger barb were embedded in paraffin following routine histological processes, stained with hematoxylin and eosin and Mallory’s trichrome techniques, and investigated by light microscopy. Histological examinations confirmed asynchronous-type ovaries resembling four different developmental stages including primary growth, cortical alveolar, vitellogenic and maturation. In the testis, primary spermatogonia, secondary spermatogonia, primary spermatocytes, secondary spermatocytes, spermatids and spermatozoa were identified. All oogenetic and spermatogenetic phases and mature germ cells occurred simultaneously in the tiger barb. This feature allows this tropical fish to breed rapidly and helps expanding its global trades.